AN ANALYSIS OF DEIXIS IN “CATCHING THE SUN” NOVEL BY TONY PARSONS - Solihah, Marâ€™atus; Susilawati, Endang; Wardah, Wardah (Journal of English Education Program, 2022)
This research is entitled “An Analysis of Deixis in Catching the Sun Novel by Tony Parsons”. It was carried out to identify the type of deixis contained in the novel and to describe to whom and what they refer to in the dialogues. The source of the data was a corpus from the dialogues in chapter 29, chapter 30, and chapter 31. This research is in qualitative form and used a descriptive method. The data obtained in this novel was in form of phrases and sentences uttered by the characters. After doing the analysis, it was found that the novel contained five types of deixis such as person deixis, spatial deixis, temporal deixis, social deixis, and discourse deixis. Person deixis was uttered 411 times, spatial deixis was uttered 24 times, temporal deixis was uttered 9 times, social deixis was uttered 3 times, and discourse deixis was uttered 15 times. The reference meanings of person deixis mostly refer to the characters, the spatial deixis refer to the places in the story, the temporal deixis refers to the time during the conversation happened, the social deixis refers to an honorable character, and the discourse deixis refers to the expressions in the same utterances uttered by the speaker. Meanwhile, the dominant type of deixis was person deixis. Hopefully, the result of this research can be useful for readers and students.Keywords: Deixis analysis, Catching the sun, Tony parsons novel, Literary works